Plastic in the ocean: How much is out there?. Issue 5 (12th October 2017) - McAdam, Ronan
Abstract : Plastic waste is found in ocean waters, on beaches and in the marine food chain. Counting it all would be impossible, but the approximate scale of the problem can be estimated.Ronan McAdam highlights the many roles of statistics in describing and tackling this global issue Abstract : Plastic waste is found in ocean waters, on beaches and in the marine food chain. Counting it all would be impossible, but the approximate scale of the problem can be estimated. Ronan McAdam highlights the many roles of statistics in describing and tackling this global issue.